The Role of Prophetic Teachings in Addressing Contemporary Global Challenges: A Comprehensive Analysis of Gender Roles and Social Justice in Islam - Mohammed Anas Ottath (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2025)
This paper explores the intersection of prophetic teachings and gender roles in Islam as they addressing to contemporary global challenges. By analysing the ethical and social principles presented by the Prophet Muhammad (peace be upon him), the study highlights how these teachings offer valuable insights for addressing modern issues such as social justice, inequality, and conflict resolution. The discussion examines how historical gender roles in early Islamic society, grounded in prophetic teachings, have evolved and how these evolving roles can contribute to contemporary discussions on gender equality. Through a nuanced examination of the Prophet’s emphasis on fairness, compassion, and respect, the paper argues that these principles can guide efforts to empower women, promote. Ethical leadership, and balance tradition with modernity. This study especially focussing on how the gender related hadith teachings being misunderstood by misinterpretations and Islamic teachings criticized as patriarchal ideology. Examining prophetic hadith with authentic narrations. Ultimately, the integration of prophetic wisdom with contemporary gender issues provides a framework for fostering a more just and equitable global society, demonstrating the relevance of Islamic teachings in addressing today’s most pressing challenges.